Pelacakan Air Tanah di Desa Mbuit Kabupaten Manggarai Barat, Provinsi Nusa Tenggara Timur - Suharji, Suharji; Nurdin, Muhammad; Karunianto, Adhika Junara; Sartapa, Sartapa; Sudarto, Slamet (BRIN Publishing, 2013)
West Manggarai Regency is a new regency as a result of regional development of Manggarai-Raya Regency. Based on information from the local mining service authorities dealing with groundwater, Mbuit village undergo clean water shortages in the dry season. One alternative to overcome the water shortages is the use of groundwater. The investigation of groundwater is intended to determine the characteristics of the geology, hydrogeology and characteristics of the electrical properties of the subsurface rocks which required to determine the potential rock layers that containing groundwater (aquifers). To achieve these objectives carried out the topography measurement, collecting data of geological/hydrogeology, and electrical resistivity measurement. Based on result of observations, analysis of the surface geological survey and supported by subsurface resistivity data in the investigation area, the potential aquifer is found. The aquifers potential has been found in a fractured aquifer system, in the northern of investigation region and distributed relatively west-east. The best aquifer is found in the line C at the point C15–C17, line G at the point G17–G18 (Humpung village), line D at the point D14–D17, line E at the point E14–E19 (Tureng village) with a resistivity value of 5–43 Wm and the depth of 50–120 meters.